School effectiveness, equity, and multilingual learners: Examining the status of multilingual learner education through school accreditation - Leah Davis (Ampersand)
The areas of school effectiveness and multilingual learner education have all garnered considerable attention in academic research; however, the exploration of the interplay between multilingual learner education and school effectiveness data remains an unexplored domain. Therefore, this qualitative case study examined multilingual learner education through a thematic analysis of accreditation reports in order to explore multilingual learner education and equity from a new viewpoint. This analysis revealed that stakeholders are aware of multilingual learners within their schools, but steps must be taken to increase equitable learning opportunities for these students through targeted professional development, collaboration, and the allocation of resources. Implications for schools, accreditation agencies, and researchers are discussed.